The marker qara in Turkic ethnonyms of the 12th century - Timokhin D.M.; Tishin V.V. (Золотоордынское обозрение)
Research Objectives: This article is devoted to the study of some aspects of the problem of the origin of ethnonyms with color markers among the nomadic Turkic-speaking peoples. They are analysed only in regard to the two-component ethnonyms where the word denoting the name of the color is used as an attributive syntactically. In the academic literature, there are several views on the practice of using such markers and various explanations of their registry and semantics. The authors of the article proceed from the consideration that any explanations being imposed universally are premature and no generalizations can help to explain all the specific examples attested in the historical and ethnographic literature. They should be viewed for each chronological period and specific region since the practice of using color markers had its own characteristics, being, apparently, due to various factors. Thus, the marker should be identified directly with narrow specific source data. Written sources, however, contain almost no direct data to help in the problem. Research Materials: The authors of the article used a Persian-language source of the 12th century, “ ʻEkd al-ʻOlā leʼl-mawkef al-aʻlā” by Afẓal al-Dīn Kermānī. Results and Novelty of the Research: Information presented in the source mentioned a rare example to allow light to be shed on a specific case. There is a passage about a group of Ghūzz had to arrive in Kermān from Khurāsān. They also are named in the text as Qarā Ghūzz. The fact allows to confirm that, at least in the second half of the 12th century among the tribes of the Oghuzs, the color marker qara was used to denote a secondary community that broke away from the initial collective, the name of which is represented by the second element of a two-component ethnonym with a color marker.